The Effect of Local Demand on Industry Location - Justman, Moshe (The Review of Economics and Statistics, 1994)
This paper compares the geographic dispersion of employment in manufacturing industries across U.S. metropolitan areas with an imputed measure of local industry demand. The results indicate that local demand has significant long-term and short-term location effects in many industries, including some with negligible transportation costs. Variation in location patterns across industries indicates that demand-side agglomeration economies and technological intensity strengthen the pull of local demand, while supply-side economies of scale and agglomeration effects weaken it. Implications are discussed with regard to international trade, technological change, industrialization and development, urban and regional issues, and industrial organization. Copyright 1994 by MIT Press.